Meister Eckhart: philosopher of christianity - Flasch, Kurt (Yale University Press, 2015)
Frontmatter -- Contents -- Translators’ Preface -- Preface -- Part One -- 1. Life and Works around 1300 -- 2. A Forgotten Concept: Philosophy of Christianity -- 3. Self-Portrayals -- 4. Beginnings: Paris and Erfurt, 1292–1298 -- 5. The Sermon Cycle on Eternal Birth -- 6. Too Grand a Plan: Prologues to the Opus tripartitum -- 7. Parisian Debates, 1302–1303 -- 8. Programmatic Speeches -- 9. Golden Apples in Silver Peels: The Origin of the World—An Explanation of Genesis -- 10. Wisdom: In Sapientiam -- 11. Departure: In Exodum -- Part Two -- 12. Interlude: Writing about Eckhart Today -- 13. Eckhart’s Intention: Commentary on John, Part 1 -- 14. Unity according to Kind: Commentary on John, Part 2 -- 15. A New Christianity for the People: German Sermons, Part I -- 16. Spicy Nutmegs: German Sermons, Part 2 -- 17. A New Consolation of Philosophy -- 18. Eckhart’s Trial: The Charges -- 19. Eckhart’s Trial: The Defense -- 20. The End in Avignon: “Devil’s Seed” -- 21. Epilogue -- Notes -- Bibliography -- Timeline -- Abbreviations -- Index